2019
DOI: 10.35564/jmbe.2019.0011
|View full text |Cite
|
Sign up to set email alerts
|

Educación Emprendedora en La Universidad

Abstract: Con el objetivo de conseguir desarrollo económico en la sociedad, y paliar problemas económicos que están surgiendo en la actualidad, como las altas tasas de desempleo juvenil, se lleva proponiendo desde hace décadas fomentar el emprendimiento y la educación emprendedora como instrumento para generar crecimiento económico en un país. Uno de los mecanismos principales según diversos autores, para generar cultura emprendedora, es la educación en centros formativos, ya que las universidades contribuyen al desarro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
0
0
2
Order By: Relevance
“…Entrepreneurial education seeks the development of multiple abilities and capacities in individuals. Training programs designed to promote entrepreneurship offer courses on the development of new business ideas, business planning, and new business models, among others (Ahmed et al, 2020;Calzado-Barbero et al, 2019). Effective entrepreneurial training enables the individual to develop the skills and access the knowledge necessary to start and grow a new business; among them: the ability to generate new business ideas the ability to recognize and pursue opportunities, the ability to lead work teams, and gather the necessary resources to achieve their objectives, among others (Ayuo et al, 2017;Calzado-Barbero et al, 2019).…”
Section: Entrepreneurial Training and Self-efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…Entrepreneurial education seeks the development of multiple abilities and capacities in individuals. Training programs designed to promote entrepreneurship offer courses on the development of new business ideas, business planning, and new business models, among others (Ahmed et al, 2020;Calzado-Barbero et al, 2019). Effective entrepreneurial training enables the individual to develop the skills and access the knowledge necessary to start and grow a new business; among them: the ability to generate new business ideas the ability to recognize and pursue opportunities, the ability to lead work teams, and gather the necessary resources to achieve their objectives, among others (Ayuo et al, 2017;Calzado-Barbero et al, 2019).…”
Section: Entrepreneurial Training and Self-efficacymentioning
confidence: 99%
“…Training programs designed to promote entrepreneurship offer courses on the development of new business ideas, business planning, and new business models, among others (Ahmed et al, 2020;Calzado-Barbero et al, 2019). Effective entrepreneurial training enables the individual to develop the skills and access the knowledge necessary to start and grow a new business; among them: the ability to generate new business ideas the ability to recognize and pursue opportunities, the ability to lead work teams, and gather the necessary resources to achieve their objectives, among others (Ayuo et al, 2017;Calzado-Barbero et al, 2019). Some empirical research carried out in Latin America context has shown that some business training programs have a favorable effect on entrepreneurial intention (e.g., Leiva et al, 2021;Lopez & Alvarez, 2019).…”
Section: Entrepreneurial Training and Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Por educación emprendedora se entiende cualquier programa pedagógico o proceso educativo tendiente a crear actitudes y habilidades empresariales (Fayolle, Gailly, & Lassas-Clerc, 2006), que tiene como fin el fomento de las competencias que se requieren para generar ideas comerciales y llevarlas a la práctica (Rae & Carswell, 2001), y capaz de desarrollar habilidades para reconocer oportunidades de negocio que otros han pasado por alto, así 3 como la autoestima para actuar donde otros dudan hacerlo (Zhang, Duysters, & Cloodt, 2014). (Para una recopilación de definiciones sobre educación emprendedora véase Calzado-Barbero et al, 2019). Si bien hay varias acepciones del término, todas tienen un eje central común: El desarrollo del espíritu emprendedor y del carácter para el emprendimiento (Calzado-Barbero, et al, 2019).…”
Section: Introductionunclassified
“…(Para una recopilación de definiciones sobre educación emprendedora véase Calzado-Barbero et al, 2019). Si bien hay varias acepciones del término, todas tienen un eje central común: El desarrollo del espíritu emprendedor y del carácter para el emprendimiento (Calzado-Barbero, et al, 2019).…”
Section: Introductionunclassified